A comparison of blocked and mixed‐trial methods for teaching auditory–visual discriminations. Issue 2 (7th December 2018) - Bentham, Stephanie N.; Walker, Stephen F.; Vander Pluym, Maria E.; Tejeda, Kristina N.
Abstract : Behavior analysts typically teach conditional discriminations in a mixed‐trial format but may switch to a blocked‐trial format for learners displaying limited acquisition. No known research has shown that mixed‐trial methods are more effective or efficient than blocked‐trial methods for teaching discriminations, so it is not clear why this format has been adopted as the "first‐line" intervention. We compared blocked and mixed‐trial formats for teaching novel auditory–visual discriminations to three adults with intellectual and developmental disabilities (IDD). Results show blocked‐trial methods resulted in faster skill acquisition in all cases, suggesting this format may be a preferable starting point for instruction.